Comparison of water- and alkali-extracted polysaccharides from Fuzhuan brick tea and their immunomodulatory effects in vitro and in vivo. Issue 2 (5th January 2022) - Sun, Yujiao; Wang, Fan; Liu, Yang; An, Yuye; Chang, Dawei; Wang, Jiankang; Xia, Fei; Liu, Ning; Chen, Xuefeng; Cao, Yungang
Abstract : Alkaline extraction can process Fuzhuan brick tea polysaccharides with a higher yield and GalA content, exhibiting promising immunomodulatory activity in vitro and in vivo . Abstract : In the present study, the purpose is to compare the effect of water extraction and alkali-assisted extraction on the structural characteristics and immunomodulatory activity of polysaccharides from Fuzhuan brick tea (FBTPs). The results indicated that water-extracted FBTPs (W-FBTPs) and alkali-extracted FBTPs (A-FBTPs) had similar molecular weights but different monosaccharide compositions, of which A-FBTPs had a higher yield and uronic acid groups corresponding to galacturonic acid (GalA). Moreover, A-FBTPs had stronger ability to promote phagocytic capacity, acid phosphatase activity and nitric oxide (NO) secretion in macrophages in vitro . In the in vivo study, A-FBTPs exhibited a promising effect to adjust the immune imbalance by enhancing the body features, antioxidant activities, immune response and intestinal mucosal barrier in cytoxan (CTX)-induced immunosuppressive mice. Besides, A-FBTP supplementation effectively improved CTX-induced gut microbiota dysbiosis, including promoting the abundance of beneficial bacteria ( e.g., Lactobacillus ) and short chain fatty acid (SCFA)-producing bacteria ( e.g., Lachnospiraceae, Prevotellaceae and Ruminococcaceae), along with reducing the growth of potentially pathogenic microbes ( e.g., Desulfovibrionaceae and Helicobacter ). These findings suggested that alkaline extraction might be a promising way to obtain high-quality acidic polysaccharides from Fuzhuan brick tea (FBT), and A-FBTPs could be developed as novel potential prebiotics and immunomodulators for further application in food formulations.